Identification of Sigma Factor σ(B)-Controlled Genes and Their Impact on Acid Stress, High Hydrostatic Pressure, and Freeze Survival in Listeria monocytogenes EGD-e - Wemekamp-Kamphuis, Henrike H. (American Society for Microbiology, 2004)
The gene encoding the alternative sigma factor σ(B) in Listeria monocytogenes is induced upon exposure of cells to several stresses. In this study, we investigated the impact of a sigB null mutation on the survival of L. monocytogenes EGD-e at low pH, during high-hydrostatic-pressure treatment, and during freezing. The survival of ΔsigB mutant exponential-phase cells at pH 2.5 was 10,000-fold lower than the survival of EGD-e wild-type cells. Moreover, the ΔsigB mutant failed to show an acid tolerance response. Upon preexposure for 1 h to pH 4.5, the survival at pH 2.5 was 100,000-fold lower for the ΔsigB mutant than for the wild type. The glutamate decarboxylase (GAD) acid resistance system is important in survival and adaptation of L. monocytogenes in acidic conditions. The σ(B) dependence of the gad genes (gadA, gadB, gadC, gadD, and gadE) was analyzed in silico. Putative σ(B)-dependent promoter sites were found upstream of the gadCB operon (encoding a glutamate/γ-aminobutyrate antiporter and a glutamate decarboxylase, respectively) and the lmo2434 gene (gadD, encoding a putative glutamate decarboxylase). Reverse transcriptase PCR revealed that expression of the gadCB operon and expression of gadD are indeed σ(B) dependent. In addition, a proteomics approach was used to analyze the protein expression profiles upon acid exposure. Although the GAD proteins were not recovered, nine proteins accumulated in the wild type but not in the ΔsigB strain. These proteins included Pfk, GalE, ClpP, and Lmo1580. Exposure to pH 4.5, in order to preload cells with active σ(B) and consequently with σ (B)-dependent general stress proteins, also provided considerable protection against high-hydrostatic-pressure treatment and freezing. The combined data argue that the expression of σ(B)-dependent genes provides L. monocytogenes with nonspecific multiple-stress resistance that may be relevant for survival in the natural environment as well as during food processing.